Aplicación web para la búsqueda centralizada de casas y apartamentos en las principales ciudades del país. House Finder - Aldana Gallo, Luisa Fernanda; Bohórquez Gamba, Edwin Alexander (Universidad Antonio Nariño, 2023)
The present document details the "House Finder" project for the specialization in software engineering at the Universidad Antonio Nariño, which aims to centralize the search for real estate in the main cities of Colombia through a web application, designed for people interested in buying, selling, or renting real estate